IMPLEMENTASI PERDA NOMOR 1 TAHUN 2012 TENTANG PAJAK DAERAH TERHADAP KEPATUHAN MEMBAYAR PAJAK BUMI BANGUNAN DI KABUPATEN TEGAL - ASLANI, ASLANI (Dinamika Hukum, 2016)
Background Local tax is one source of revenue is important and a potential addition to other sources of income, namely oil and gas revenues and non-tax revenues due to the number of population is so large and the area is so large, the Tegal has tax sources very much. Receipts from taxes is then used by the government to build infrastructure in the public interest. In other words, the local revenue from taxes is a "driving force" of economic life of society which is the real means for the government to be able to provide a wide range of facilities and infrastructure in the public interest. The purpose of this study to know the Implementation Regulation No. 1 Year 2012 on Regional Tax Compliance Against Paying Property Tax in Tegal regency. And the obstacles that arise in the implementation of Regulation No. 1 Year 2012 on Regional Tax Compliance Against Paying Property Tax in Tegal regency. This type of research used juridical Empirical research of this kind. Type juridical, as research starts by using legal norms, especially from the point of law Implementation Regulation No. 1 Year 2012 on Regional Tax Compliance Against Paying Property Tax in Tegal regency. Data collection techniques that the study of literature, documents and interviews. The results of the study Implementation Regulation No. 01 Year 2012 on Regional Taxes on adherence to pay property tax in Tegal, it can be seen in the name, the object and the subject of property taxes is regulated in Article 58 s / d Section 60 of the Local Taxes. Further assessment of building tax as stipulated in Article 61 through Article 64 and the procedures for the collection of property taxes rural and urban described at 65 and Article 66. Regional Regulation on Local Taxes have become a guideline for both local government and community Tegal regency in the discharge of liabilities in Taxation, especially regarding local taxes. Results of local tax revenue, together with other elements of the reception area, in turn, will be employed to administer the affairs of the authority area in accelerating the prosperity of local communities Tegal. constraints experienced in the implementation of law No. 01 of 2012 on Regional Taxes on adherence pay taxes property taxes in Tegal regency, namely: a) a lack of understanding and awareness of the taxpayer, b) the level of income of the taxpayer. To overcome the obstacles in the realization of tax compliance earth and buildings with several ways: a) socialization of the government, b) to check the tax rate. Keywords : local regulation, local tax, property tax